2023
DOI: 10.1007/s11096-023-01571-3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for providing self-care advice in community pharmacies: a qualitative study

Abstract: Background Community pharmacies are easily accessible for self-care advice. Guidelines for providing self-care advice were introduced in several countries, including the Netherlands in the 1990s. Previous studies have indicated room for improvement in self-care advice in daily pharmacy practice. Aim To identify barriers and facilitators for providing self-care advice. Method Semi-structured interviews were conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previously published studies have shown, however, that external evidence in particular is only sparsely integrated into everyday counselling [ 9 18 ]. Barriers such as a lack of time and missing information resources were identified as the main reason causing the evidence-to-practice gap [ 19 24 ]. So far, very few measures have been introduced to bridge this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies have shown, however, that external evidence in particular is only sparsely integrated into everyday counselling [ 9 18 ]. Barriers such as a lack of time and missing information resources were identified as the main reason causing the evidence-to-practice gap [ 19 24 ]. So far, very few measures have been introduced to bridge this gap.…”
Section: Introductionmentioning
confidence: 99%